Effect of drying techniques on browning index, phenolic compounds, polysaccharides, triterpenoids and antioxidant activity of tiger milk mushroom (Lignosus rhinocerus) sclerotium - Soontharapirakkul, Kanteera; Kotpat, Thidaporn (Agriculture and Natural Resources, 2023)
Importance of the work: Drying is one method for preserving medicinal mushrooms. Many studies have found that different drying techniques affect bioactive compounds and biological activity of the product. However, the effect of drying the tiger milk mushroom (Lignosus rhinocerus) sclerotium has not been studied. Objectives: To investigate drying techniques to produce a high content of bioactive compounds and levels of antioxidant activity in the tiger milk mushroom sclerotium. Materials & Methods: The sliced sclerotium samples were dried using seven drying techniques: sun drying (SD), shade drying (SHD), freeze-drying (FD), oven drying at 40°C (OD40), oven drying at 70°C (OD70), light dry roasting (LDR), and dark dry roasting (DDR) Subsequently the dried samples were milled into individual powders. Next, the dried samples were extracted with boiling water and analyzed for browning index, total phenolic, total flavonoid, total polysaccharide content and antioxidant activity compared to the fresh sample (FSH). Results: The DDR and OD70 techniques showed high values for the browning index and antioxidant activity (based on 2,2-diphenyl-1-picrylhydrazyl hydrate and ferric reducing antioxidant power analysis) and for the total phenolic, total flavonoid and total polysaccharide contents. In contrast, the total protein content was high in the low-temperature drying samples (FSH, SD, SHD, LDR and FD). The highest total triterpenoid content (mean ± SD; 14.52 ± 0.57 mg ursolic acid/g of dry basis) was obtained in the OD40 sample. Main finding: DDR was a potent drying technique that enhanced the total phenolic, total flavonoid and total polysaccharide contents, as well as antioxidant activity. Thus, using the DDR technique may be the most appropriate option to preserve the quality of the sclerotium of the tiger milk mushroom for commercialization as a medicinal mushroom powder for infusion.